Comunicación, posdesarrollo y decolonialidad. Debates urgentes en escenario de crisis civilizacional. - BELMONTE, Valeria (Chasqui (13901079))
One of the challenges that the crisis of civilization imposes on critical communication sciences in the region is the expansion of its politicaltransformative horizon outside the epistemic matrix of capitalist modernity. Such expansion becomes urgent given the dimension of the crisis. Criticism of development in its predatory nature and thinking about alternatives as a present issue in current critical social studies, questions the communication agenda in Latin America in a decolonial key. The notions of postdevelopment and good living/living well, within that critique, allow us to think of post-Western communication in post-development times: a communication model that is removed from the ordering of the modern-Western world. Thus, communicational decoloniality is pointed out as a political-epistemic option that emerges before the civilizational transition.